Lysophosphatidic acid induces integrin activation in vascular smooth muscle and alters arteriolar myogenic vasoconstriction - Staiculescu, Marius C.; Ramirez-Perez, Francisco I.; Castorena-Gonzalez, Jorge A.; Hong, Zhongkui; Sun, Zhe; Meininger, Gerald A.; Martinez-Lemus, Luis A. (Frontiers in Physiology, 2014)
In vascular smooth muscle cells (VSMC) increased integrin adhesion to extracellular matrix (ECM) proteins, as well as the production of reactive oxygen species (ROS) are strongly stimulated by lysophosphatidic acid (LPA). We hypothesized that LPA-induced generation of ROS increases integrin adhesion to the ECM. Using atomic force microscopy (AFM) we determined the effects of LPA on integrin adhesion to fibronectin (FN) in VSMC isolated from rat (Sprague–Dawley) skeletal muscle arterioles. In VSMC, exposure to LPA (2µM) doubled integrin-FN adhesion compared to control cells (P<0.05). LPA-induced integrin-FN adhesion was reduced by pre-incubation with antibodies against β1 and β3 integrins (50µg/ml) by 66% (P<0.05). Inhibition of LPA signaling via blockade of the LPA G-protein coupled receptors LPAR1 and LPAR3 with Ki16425 (10µM) reduced the LPA-enhanced adhesion of VSCM to FN by 40% (P<0.05). Suppression of ROS with tempol (250µM) or apocynin (300µM) also reduced the LPA-induced FN adhesion by 47% (P<0.05) and 59% (P<0.05), respectively. Using confocal microscopy, we observed that blockade of LPA signaling, with Ki16425, reduced ROS by 45% (P<0.05), to levels similar to control VSMC unexposed to LPA. In intact isolated arterioles, LPA (2µM) exposure augmented the myogenic constriction response to step increases in intraluminal pressure (between 40-100mm Hg) by 71% (P<0.05). The blockade of LPA signaling, with Ki16425, decreased the LPA-enhanced myogenic constriction by 58% (P<0.05). Similarly, blockade of LPA-induced ROS release with tempol or gp91 ds-tat decreased the LPA-enhanced myogenic constriction by 56% (P<0.05) and 55% (P<0.05), respectively. These results indicate that, in VSMC, LPA-induced integrin activation involves the G-protein coupled receptors LPAR1 and LPAR3, and the production of ROS, and that LPA may play an important role in the control of myogenic behavior in resistance vessels through ROS modulation of integrin activity.